Low temperature thermochemical surface treatment of austenitic stainless steel for improved mechanical and tribological - Triwiyanto , Askar; Mridha , Shahjahan; Haruman, Esa (Trans Tech Publications, Switzerland, 2010)
This paper describes the results of four thermochemical surface treatments of austenitic stainless steels carried out at 450oC in a fluidised bed furnace and they are nitriding, carburizing and the newly developed hybrid process involving the simultaneous and sequential incorporation of nitrogen and carbon to form a dual layer structure in order to achieve much enhanced surface hardness and wear resistance without compromising the corrosion resistance of the steel. In all these treatments there formed alloyed layers with a common feature of being precipitation-free and supersaturated with nitrogen, or carbon or both in the austenite lattice which is known as S Phase or expanded austenite. However the layer thickness was not uniform in any of these treatments and an effective layer was produced after 8h treatment duration. The nitriding treatment produced thicker and harder layer compared to other treatments; the maximum hardness was over 1500 Hv for nitriding and the minimum hardness of 500 Hv for carburizing treatment. The nitriding treatment sample gave high wear resistance which corresponded to high hardness values.